2007
DOI: 10.1785/0120050632
|View full text |Cite
|
Sign up to set email alerts
|

Rupture Kinematics of the 2005Mw 8.6 Nias–Simeulue Earthquake from the Joint Inversion of Seismic and Geodetic Data

Abstract: The 2005 M w 8.6 Nias-Simeulue earthquake was caused by rupture of a portion of the Sunda megathrust offshore northern Sumatra. This event occurred within an array of continuous Global Positioning System (GPS) stations and produced measurable vertical displacement of the fringing coral reefs above the fault rupture. Thus, this earthquake provides a unique opportunity to assess the source characteristics of a megathrust event from the joint analysis of seismic data and near-field static co-seismic displacements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 35 publications
13
165
2
1
Order By: Relevance
“…velocity model), the method assumes implicitly that the major part of afterslip and the seismicity occurs on or close to (Hsu et al 2006) and aftershocks shown for the same 11 months period after the mainshock. Grey lines indicate co-seismic slip distribution (2.5-m slip contours, Konca et al 2007). the subduction interface.…”
Section: Methods 2: Calculation Of Afterslip To Aftershocks Ratio (Asar)mentioning
confidence: 99%
“…velocity model), the method assumes implicitly that the major part of afterslip and the seismicity occurs on or close to (Hsu et al 2006) and aftershocks shown for the same 11 months period after the mainshock. Grey lines indicate co-seismic slip distribution (2.5-m slip contours, Konca et al 2007). the subduction interface.…”
Section: Methods 2: Calculation Of Afterslip To Aftershocks Ratio (Asar)mentioning
confidence: 99%
“…These added observations allow us to model the possible locations and sizes of this SSE, both with improved constraints. [Konca et al, 2007]. Part of this section ruptured during the 2010 M w 7.8 Banyak Islands earthquake (source model from the U.S. Geological Survey: http://earthquake.usgs.gov/earthquakes/ eventpage/usp000hat0#scientific_finitefault).…”
Section: Introductionmentioning
confidence: 99%
“…One fundamental question which this paper seeks to answer is: Can seismic data provide sufficiently accurate models of the slip distributions of large tsunamigenic earthquakes to be reliably used in teletsunami modelling? While both seismic (KIKUCHI and KANAMORI, 1991) and tsunami (SATAKE, 1987) data are routinely used separately to estimate slip distributions for large earthquakes, they are rarely used together (see, however, SATAKE, 1993;TANIOKA et al, 1995;JOHNSON et al, 1996;KONCA et al, 2007;SATAKE and TANIOKA, 1995;DELOUIS et al, 2002;KOKETSU et al, 2004;ICHINOSE et al, 2005 andCHLIEH et al, 2007, for examples of joint inversion using various combinations of seismic, tsunami and geodetic data). One reason for this is that tsunami data have hitherto been taken from coastal tide gauges, which can be very sensitive to the shallow bathymetry in their immediate vicinity.…”
Section: Introductionmentioning
confidence: 99%